Visual perception of axes of head rotation - Arnoldussen, David M.; Goossens, Jeroen; Van Den Berg, Albert (Frontiers in Behavioral Neuroscience, 2013)
Registration of ego-motion is important to accurately navigate through space. Movements of the head and eye relative to space are registered through the vestibular system and optical flow, respectively. Here, we address three questions concerning the visual registration of self-rotation. 1. Eye-in-head movements provide a link between the motion signals received by sensors in the moving eye and sensors in the moving head. How are these signals combined into an ego-rotation percept? We combined optic flow of simulated forward and rotational motion of the eye with different levels of eye-in-head rotation for a stationary head. We dissociated simulated gaze rotation and head rotation by different levels of eye-in-head pursuit. We found that perceived rotation matches simulated head- not gaze-rotation. This rejects a model for perceived self-rotation that relies on the rotation of the gaze line. Rather, eye-in-head signals serve to transform the optic flow’s rotation information, that specifies rotation of the scene relative to the eye, into a rotation relative to the head. This suggests that transformed visual self-rotation signals may combine with vestibular signals. 2. Do transformed visual self-rotation signals reflect the arrangement of the semicircular canals (SCC)? Previously, we found sub-regions within MST and V6+ that respond to the speed of the simulated head rotation. Here, we re-analyzed those BOLD signals for the presence of a spatial dissociation related to the axes of visually simulated head rotation, such as have been found in sub-cortical regions of various animals. Contrary, we found a rather uniform BOLD response to simulated rotation along the three SCC axes. 3. We investigated if subject’s sensitivity to the direction of the head rotation axis shows SCC axes specifcity. We found that sensitivity to head rotation is rather uniformly distributed, suggesting that in human cortex, visuo-vestibular integration is not arranged into the SCC frame.